2015
DOI: 10.1038/srep08878
|View full text |Cite
|
Sign up to set email alerts
|

Common marmosets show social plasticity and group-level similarity in personality

Abstract: The social environment influences animal personality on evolutionary and immediate time scales. However, studies of animal personality rarely assess the effects of the social environment, particularly in species that live in stable groups with individualized relationships. We assessed personality experimentally in 17 individuals of the common marmoset, living in four groups. We found their personality to be considerably modified by the social environment. Marmosets exhibited relatively high plasticity in their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
87
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 80 publications
(104 citation statements)
references
References 55 publications
(70 reference statements)
13
87
4
Order By: Relevance
“…Conversely, our finding contradicts some other studies which found that, for example, in sticklebacks ( Gasterosteus aculeatus ) the repeatability of boldness was affected by social conditions (Jolles et al. ) and in marmosets ( Callithrix jacchus ) explorative tendencies were less repeatable when individuals were tested alone compared to individuals tested in the presence of conspecifics (Koski and Burkart ).…”
Section: Discussioncontrasting
confidence: 99%
“…Conversely, our finding contradicts some other studies which found that, for example, in sticklebacks ( Gasterosteus aculeatus ) the repeatability of boldness was affected by social conditions (Jolles et al. ) and in marmosets ( Callithrix jacchus ) explorative tendencies were less repeatable when individuals were tested alone compared to individuals tested in the presence of conspecifics (Koski and Burkart ).…”
Section: Discussioncontrasting
confidence: 99%
“…Consistent with past research (Inoue‐Murayama et al., ; Iwanicki & Lehmann, ; Koski & Burkart, ; Koski et al., ; Šlipogor et al., ), we found moderate to large reaction norm intercept repeatability (Rnormalintercepttrue~ range: 0.33–0.91; see Figure a), providing evidence for personality across observational periods. As expected given our short focal sampling duration and observational methodology, which generally produce high observation–level variance (Martin & Suarez, ), long‐term (Rnormallongtermtrue~ range: 0.04–0.31) and short‐term (Rnormalshortermtrue~ range: 0.06–0.38) repeatability estimates were low to moderate.…”
Section: Resultssupporting
confidence: 91%
“…Agonistic behavior was very rare and therefore not included in the analysis. All observations were performed by the same observer using an established protocol (see also Koski and Burkart [65]; a test for interobserver reliability with an independent observer resulted in 0.89% of agreement). An average of 173 ± 3.48 observation minutes was available for each individual.…”
Section: Methodsmentioning
confidence: 99%